“Finding my way in a maze while the clock is ticking”: The daily life challenges of adolescents and young adults with an uncertain or poor cancer prognosis - Burgers, Vivian W. G.; van den Bent, Martin J.; Dirven, Linda; Lalisang, Roy I.; Tromp, Jacqueline M.; Compter, Annette; Kouwenhoven, Mathilde; Bos, Monique E. M. M.; de Langen, Adrianus; Reuvers, Milou J. P.; Franssen, Suzanne A.; Frissen, Simone A. M. M.; et al. (Frontiers in Oncology, 2022)
Introduction: Increasingly more adolescent and young adult (AYA; aged 18-39 years) patients with an uncertain and/or poor cancer prognosis (UPCP) are gaining life years because of novel treatments or refinement of established therapies, and sometimes even face the prospect of long-term disease control. This study aims to examine the challenges of AYAs with a UPCP in daily life to inform the development of AYA care programs. Methods: Semi-structured in depth interviews were conducted among AYAs with a UPCP. Since we expected differences in experiences between three AYA subgroups we interviewed patients of these subgroups: (1) traditional survivors, (2) low-grade glioma survivors and (3) new survivors. Interviews were analyzed using elements of grounded theory. AYA patients were actively involved as research partners. Results: In total 46 AYAs with UPCP participated and shared their challenges in daily life. They were on average 33.4 years old (age range 23-44) and most of them were female (63%). Most common tumor types were low-grade gliomas (16), sarcomas (7), breast cancers (6) and lung cancers (6). We identified five primary themes: (1) feeling inferior to previous self and others (e.g. feeling useless, who wants me in a relationship, (2) feeling of being alone (e.g. lonely thoughts, nobody really gets me), (3) ongoing confrontation (e.g. it is always there, own decline), (4) grief about life (e.g. grief about life I did not get, grief about old life), and (5) loss of control over the future (e.g. not able to make future plans, waiting for growth). Although all of the challenges were identified in the three AYA sub-groups, the perceived intensity of the challenges differed slightly between the subgroups. Discussion: AYAs living with a UPCP experience challenges associated to their sense of altered identity, their position in the social network and the future uncertainties. This study highlights the importance to recognize and acknowledge the unique challenges of this group. To provide age-specific care it is important to embed acceptance and commitment therapy and AYA peer support within the healthcare system and other care programs to support AYAs to live well with their disease.